2019
DOI: 10.1111/cea.13527
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal eosinophilia accompanies food allergy to hen egg white protein in young pigs

Abstract: Clin Exp Allergy. 2020;50:95-104. wileyonlinelibrary.com/journal/cea | 95 Abstract Background: Esophagitis with eosinophilia, inflammation, and fibrosis represent a chronic condition in humans with food allergies.Objective: In this investigation, we asked whether esophagitis with an eosinophilic component is observed in young pigs rendered allergic to hen egg white protein (HEWP). Methods:Food allergy was induced in young pigs using two protocols. In one protocol, sensitized pigs were challenged by gavage with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…10). In the next phase, an animal feasibility study will be conducted in a swine model expressing esophageal strictures (and potentially esophageal eosinophilia [143]) in vivo. A first-in-human study in healthy subjects and EoE patients will then conclude the second phase of the project.…”
Section: Discussionmentioning
confidence: 99%
“…10). In the next phase, an animal feasibility study will be conducted in a swine model expressing esophageal strictures (and potentially esophageal eosinophilia [143]) in vivo. A first-in-human study in healthy subjects and EoE patients will then conclude the second phase of the project.…”
Section: Discussionmentioning
confidence: 99%
“…Some sounded a cautionary note-that reintroduction failure after tolerating a food challenge in adults is common, increases over time and is primarily due to atypical symptoms 84 and that anaphylaxis during food challenge may be refractory to intramuscular adrenaline, suggesting that protocols to guide the careful use of peripherally administered intravenous adrenaline may be advisable in food challenge units, for use in these rare cases of refractory anaphylaxis. 85 Other pre-clinical studies support the development of new biomarkers for improved food allergy diagnosis 86,87 and the development of new ways to prevent and treat food allergy. [88][89][90]…”
Section: Foodchalleng E Smentioning
confidence: 99%
“…46 Plundrich and colleagues examined whether food (hen egg white protein) induced allergy in young pigs induced an EoE like phenotype. 47 The advantage of the pig system is that pig oesophagus is anatomically similar to humans, non-keratinized and display oesophageal submucosal glands and is similar in size to the human oesophagus allowing for the use of endoscopy. 48 The authors showed that challenge of hen Collectively, these studies suggest that the pig may be an effective model to study immunological processes that drive some EoEassociated oesophageal epithelia remodelling features and to study the role of the underlying oesophageal inflammatory component in EoE with endoscopic features.…”
Section: New Model Of Eosinophilic Oesophagitismentioning
confidence: 99%
“…However, the oesophagus of the mouse is anatomically different to human (keratinized versus non‐keratinized) which greatly limits interpretation and translatability of studies derived from using this animal model system 46 . Plundrich and colleagues examined whether food (hen egg white protein) induced allergy in young pigs induced an EoE like phenotype 47 . The advantage of the pig system is that pig oesophagus is anatomically similar to humans, non‐keratinized and display oesophageal submucosal glands and is similar in size to the human oesophagus allowing for the use of endoscopy 48 .…”
Section: Experimental Models Of Allergic Diseasementioning
confidence: 99%